Achieving business competitiveness through corporate social responsibility and dynamic capabilities: An empirical evidence from emerging economy. (1st February 2023) - Sarwar, Huma; Aftab, Junaid; Ishaq, Muhammad Ishtiaq; Atif, Muhammad
Abstract: The automobile industry is adopting various processes, including innovation and dynamic capabilities, to foster economic growth and survival without negatively affecting the environment. This study investigates the indirect role of green innovation and environmental performance in the relationships of corporate social responsibility and dynamic capabilities with business competitiveness. Additionally, this research explores government support as a boundary condition in strengthening (or vice versa) the impact of dynamic capabilities and corporate social responsibility on green innovation. We used a self-administered survey questionnaire to collect data from 344 respondents in Pakistan's automobile industry. The structural equation modeling results revealed that green innovation and environmental performance act as mediators and government support strengthens dynamic capabilities and corporate social responsibility connection with green innovation. The theoretical and practical implications for practicing managers are thoroughly discussed.